2018
DOI: 10.1111/ejed.12294
|View full text |Cite
|
Sign up to set email alerts
|

Children's rights and their subjective well‐being from a multinational perspective

Abstract: This article explores the relationship between children's knowledge and perceptions about their rights and subjective well-being (SWB) in a sample of 8-, 10-and 12-yearolds in 18 countries, taking account of gender differences. Children's knowledge and perceptions about their rights were analysed considering whether they reported that they knew their rights, whether they had heard about the UN Convention on the Rights of the Child (CRC) and whether they thought that, in their country, adults respected their ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…& Health: Several health-related factors including physical fitness (positive association) and illness or disease (negative association) have been found to relate to children's LS (Marques et al 2017;Klocke et al 2014;Kleszczewska et al 2018;Haanpää et al 2018;Lew et al 2018). & Time use (including ICT use): Time use, particularly in relation to ICT use, has been found to predict variation in LS, and also varies according to gender, thus potentially explaining gender differences in LS (Rees 2017;Larson and Verma 1999;Amin and Chandrasekhar 2012;Ersado 2005;Dornan and Woodhead 2015;Iannotti et al 2009;Fergusson et al 2015;Boniel-Nissim et al 2015) & Rights: Children's awareness of their rights as children and, especially, perceiving that these rights are respected by adults are positively associated with SWB (Casas et al 2018). & Gender and sexuality: Gender differences are common in studies of SWB (Rees and Main 2015).…”
Section: Other Factorsmentioning
confidence: 99%
“…& Health: Several health-related factors including physical fitness (positive association) and illness or disease (negative association) have been found to relate to children's LS (Marques et al 2017;Klocke et al 2014;Kleszczewska et al 2018;Haanpää et al 2018;Lew et al 2018). & Time use (including ICT use): Time use, particularly in relation to ICT use, has been found to predict variation in LS, and also varies according to gender, thus potentially explaining gender differences in LS (Rees 2017;Larson and Verma 1999;Amin and Chandrasekhar 2012;Ersado 2005;Dornan and Woodhead 2015;Iannotti et al 2009;Fergusson et al 2015;Boniel-Nissim et al 2015) & Rights: Children's awareness of their rights as children and, especially, perceiving that these rights are respected by adults are positively associated with SWB (Casas et al 2018). & Gender and sexuality: Gender differences are common in studies of SWB (Rees and Main 2015).…”
Section: Other Factorsmentioning
confidence: 99%
“…This cross-sectional study enhances previous knowledge about the role of rights’ fulfillment in psychological functioning outcomes (Casas et al, 2018; Kutsar et al, 2019) in RC (Magalhães et al, 2018) by exploring the moderating role of supportive relationships and the association between rights’ fulfillment and youth psychological outcomes. This is a Portuguese based study, a context where the out-of-home care system is significantly different when compared to other European or US contexts (Del Valle & Bravo, 2013; ISS, 2019), as it is based mainly on RC.…”
Section: Current Studymentioning
confidence: 63%
“…Furthermore, studies with normative samples suggest that greater well-being is reported by youth who perceive that their rights are respected (Casas et al, 2018), and specifically the rights of protection, participation, and non-discrimination (Kutsar et al, 2019). It is expected that when young people feel that they are protected, cared about, listened to or treated fairly, their well-being is greater (Kutsar et al, 2019).…”
Section: Young People’s Rights and Psychological Functioning In Residential Carementioning
confidence: 99%
See 1 more Smart Citation
“…A study of over 14,000 adolescents showed strong correlations between victimization and a loss of belief in others, alongside an increase in suicidality (Fullchange & Furlong, 2016); thus, youth may have benefited by rebuilding trust in adults and this may have played a role in the increases in perceptions of a positive school climate and greater social cohesion. Alternatively, as children become aware of their rights and see these being promoted by adults, their wellbeing also increases (Casas, González-Carrasco, & Luna, 2018).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%